2009
DOI: 10.1371/journal.pone.0005482
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Neuroinflammation Promotes Parkinsonism in Rats

Abstract: BackgroundSporadic Parkinson's disease (PD) is a progressive neurodegenerative disorder with unknown cause, but it has been suggested that neuroinflammation may play a role in pathogenesis of the disease. Neuroinflammatory component in process of PD neurodegeneration was proposed by postmortem, epidemiological and animal model studies. However, it remains unclear how neuroinflammatory factors contribute to dopaminergic neuronal death in PD.FindingsIn this study, we analyzed the relationship among inducible nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 58 publications
5
67
0
Order By: Relevance
“…Results were analyzed by two-way ANOVA followed by the Bonferroni's test [9,16]. Although, several others indicated that LPS injections unilaterally [1,28,29] or bilaterally [30,31] in the striatum [32] and intrapallidal [33] produces a decrease in nigral and striatal DA and DOPAC levels and induces locomotor deficits. Most likely, such behavioral differences occurred due to the differential site injections adopted in each study.…”
Section: Discussionmentioning
confidence: 99%
“…Results were analyzed by two-way ANOVA followed by the Bonferroni's test [9,16]. Although, several others indicated that LPS injections unilaterally [1,28,29] or bilaterally [30,31] in the striatum [32] and intrapallidal [33] produces a decrease in nigral and striatal DA and DOPAC levels and induces locomotor deficits. Most likely, such behavioral differences occurred due to the differential site injections adopted in each study.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have injected this region with LPS and observed decreases in SN DA neuron soma, reduced striatal dopamine, and production of proinflammatory cytokines. [38][39][40] Furthermore, this procedure is reported to result in buildup of alpha-synuclein in the soma of DA neurons and deficits in motor performance. [38][39][40] This indicates that inflammatory response in the striatum causes insult that is transmitted to the neuronal soma in the SN or that the inflammatory reaction is not confined to the striatum and encompasses the SN.…”
Section: Bacterial Lps-based Inflammatory Response Modeling Of Pdmentioning
confidence: 99%
“…It has been well documented that inflammation plays an important role in the pathogenesis and severity of PD [2,3]. Several lines of research have shown that serum oxidative stress and proinflammatory cytokines, such as interleukin (IL)-1b, IL-2, IL-6, HLA-DRB1, tumor necrosis factor (TNF)-α, mitochondrial dysfunction and activated microglia, are elevated in the brain and cerebral spinal fluid of PD patients [4,5,6]. …”
Section: Introductionmentioning
confidence: 99%